Tracking Learning and Teaching Chains and Their Variations in the Development of Mixed-Methods Methodology - Harri Pitkäniemi (Educational Process: International Journal)
Recently, inspirational articles on research methodology have been written on the development of the mixed-methods approach. This area of study concerns methodological trends in the construction of research designs. One may ask, whether it is possible to construct a notional piece of investigation, potentially highlighting a research design that successfully seeks to identify a causal mechanism. The purpose of the current study is to consider how to construct a research design that would illustrate the application of methodological ideas in the context of educational research, such as school education and learning. This study produces three dimensions of causal mechanism: a horizontal dimension (chain length), a vertical dimension (possibilities of different variations), and tentatively a hypothetical causal network dimension (including context factors).